Drama for students. presenting analysis, context and criticism on commonly studied dramas - Hacht, Anne Marie (Gale virtual reference library, 2005)
Provides critical overviews of the most-studied plays of all time periods, nations, and cultures. Includes discussions of themes, characters, critical reception, dramatic devices and traditions as well as cultural and historical context.